ANALISIS KAJIAN FEMINISME PADA PUISI “LUKISAN BEWARNA” - Kristina Br Purba (JOURNAL SAINS STUDENT RESEARCH, 2026)
This study aims to analyze the feminist values ​​in the poem "Lukisan Bewarna" by Joko Pinurbo using a literary feminist approach. This poem was chosen because it presents poetic symbols that represent emotional experiences, freedom of expression, and women's position in social life. The research method used is descriptive qualitative with data collection techniques in the form of literature reviews and documentation of poetry texts. Data were analyzed through in-depth reading of the poem's verses that describe women's experiences, feelings, and representations. The results show that the poem "Lukisan Bewarna" represents feminism implicitly through metaphors of color, nature, and complex emotional expressions. Women are depicted as empowered, creative, and resilient subjects, not as passive objects in a patriarchal structure. In conclusion, this poem emphasizes the importance of recognizing the existence and experiences of women as whole individuals, while also showing that feminist values ​​can be conveyed through gentle and humanistic poetic language in literary works.